2009
DOI: 10.1111/j.1365-2958.2009.06919.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA relaxation‐dependent phase biasing of the fim genetic switch in Escherichia coli depends on the interplay of H‐NS, IHF and LRP

Abstract: SummaryReversible inversion of the DNA element fimS is responsible for the phase variable expression of type 1 fimbriae in Escherichia coli. The FimB tyrosine integrase site-specific recombinase inverts fimS in the on-to-off and off-to-on directions with approximately equal efficiencies. However, when DNA supercoiling is relaxed, fimS adopts predominantly the on orientation. This orientational bias is known to require binding of the nucleoid-associated protein LRP within fimS. Here we show that binding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 43 publications
2
83
0
Order By: Relevance
“…E. coli HNS binds to fimS-IRL (inverted repeat left) which influences site-specific recombination and thus decreases fimA promoter activity (O'Gara & Dorman, 2000;Corcoran & Dorman, 2009). We have shown that the expression of hns is increased by PecS (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…E. coli HNS binds to fimS-IRL (inverted repeat left) which influences site-specific recombination and thus decreases fimA promoter activity (O'Gara & Dorman, 2000;Corcoran & Dorman, 2009). We have shown that the expression of hns is increased by PecS (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The fimS switch, which alternates bacteria between type 1 fimbriated and non-fimbriated states, is controlled by site-specific recombinases FimB and FimE (McClain et al, 1991). The interplay of DNA binding proteins HNS, IHF and Lrp also influences the fimS orientation (Corcoran & Dorman, 2009). Originally characterized in Klebsiella strains, type 3 fimbriae provide the bacteria with the ability to adhere to epithelial cells of the respiratory and urinary tracts (Hornick et al, 1992;Tarkkanen et al, 1997;Jagnow & Clegg, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This might also apply to integrative recombination catalyzed by the phage λ integrase (Thompson et al 1988;Crisona et al 1999), as well as other reactions catalyzed by the members of integrase superfamily of site-specific recombinases (Abremski and Hoess 1985;Dove and Dorman 1994;Corcoran and Dorman 2009). On the other hand, the recombination by C-terminally-modified SSV1 virus integrase from a thermophilic archaeon characterized by positively supercoiled DNA is more efficient with fully relaxed/linear DNA substrates, and is also directionally highly promiscuous in vitro (Muskhelishvili et al 1993), implicating additional, presently unknown, factors in imparting directionality on the SSV1 integrase-driven recombination in vivo (Schleper et al 1992).…”
Section: H-ns Nucleoprotein Complexesmentioning
confidence: 99%
“…Corroborating the molecular pathogenesis studies of type 1 pili in UTI, vaccination with pili subcomponents in animal studies has been shown to reduce the severity and duration of infection (Palaszynski et al, 1998). Type 1 pili are encoded by the fim operon (fimAICDFGH) and their expression is controlled at multiple regulatory levels (Corcoran & Dorman, 2009;Kelly et al, 2006;McClain et al, 1991). The orientation of the invertible type 1 pili promoter region (fimS) (Abraham et al, 1985) is determined by the action of multiple tyrosine recombinases.…”
Section: Introductionmentioning
confidence: 99%